2008
DOI: 10.3325/cmj.2008.4.528
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Among School Children in Postwar Bosnia and Herzegovina: Cross-Sectional Study

Abstract: Aim To compare the prevalence and characteristics of bullying between two towns in Bosnia and Herzegovina -Stolac, which was exposed to firearm conflict during the 1992-1995 war in Bosnia and Herzegovina, and Posušje, which was outside of the active combat zone. MethodsIn this cross-sectional study, we included 484 primary school pupils attending 4th-8th grade of elementary school, 217 (44.8%) of them from Stolac and 267 (55.2%) from Posušje. The pupils were interviewed using a standardized questionnaire on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
2
12
2
1
Order By: Relevance
“…Among the analyzed variables of sex, age, town, and school achievement, only male sex was a significant predictor of bullying, increasing the relative risk by 3,005 times. They concluded that bullying among primary school pupils did not differ between areas that experienced war activities in 1992-1995 (41). Their results differed in relation to the results of a study conducted in Croatia, which showed that primary school children from a town exposed to war perceived themselves as more aggressive in their early adolescence than their peers from a town that was not exposed to war (42).…”
Section: Behavioral Problemscontrasting
confidence: 55%
“…Among the analyzed variables of sex, age, town, and school achievement, only male sex was a significant predictor of bullying, increasing the relative risk by 3,005 times. They concluded that bullying among primary school pupils did not differ between areas that experienced war activities in 1992-1995 (41). Their results differed in relation to the results of a study conducted in Croatia, which showed that primary school children from a town exposed to war perceived themselves as more aggressive in their early adolescence than their peers from a town that was not exposed to war (42).…”
Section: Behavioral Problemscontrasting
confidence: 55%
“…There are strong indications that bullying is a problem in many countries of the world (Smith et al 1999). Data have accumulated from a lot of European countries such as Bosnia and Herzegovina (Obrdalj and Rumboldt 2008), Finland (Kumpulainen and Rasanen 2000;Klomek et al 2008), Greece (Pateraki and Houndoumadi 2001), Italy (Gini 2004), Norway (Hansen et al 2008;Olweus 1994), Spain (Barrio et al 2008), Sweden (Holmberg and Hjern 2008) and the UK (Glover et al 2000). There have also been reports from Australia (Rigby et al 1991), Canada (Bentley and Li 1995), India (Khatri and Kupersmidt 2003), Japan (Crystal 1994), the USA (Berthold and Hoover 2000) and Zambia (Nabuzoka 2003).…”
Section: Introductionmentioning
confidence: 89%
“…Bosnia and Herzegovina has been affected by recent war from 1992 to 1995 including civilian victims, displacement of people and refugees, still missing people including children [17][18][19][20]. Cunha et al [21], in their review about problem of aging human remains and living individuals which exposed the experience of the authors working in the Forensic Anthropology Society of Europe subsection of the International Academy of Legal Medicine, suggested that age estimation should be brought up to date on the usage of known methods provided by literature and development of new methods and to more precisely discuss the results in the specific population in order to use the most adequate technique.…”
Section: Introductionmentioning
confidence: 99%